Business students' thinking about their studies and future careers. (2nd July 2020) - Bennett, Dawn; Knight, Elizabeth; Jevons, Colin; Ananthram, Subramaniam
ABSTRACT: The enduring employability of twenty-first-century workers demands explicit and career-long attention. As a result, higher education finds itself tasked with enabling students to negotiate their career-long cognitive and social development as professionals and social citizens. Grounded in social cognitive theory, the study reported here seeks to understand students' career-related development. The participants reported in this article are 6, 004 undergraduate business students enrolled with one of 32 Australian universities. The students created personalised employability profiles using an online tool. Drawing from the tool's data, the article reports students' text-based responses to the question of what they would change about their degree programmes. Students express concerns about the potential to establish a career as early as the first year of study. The findings suggest the value of adopting a research-informed, metacognitive approach to employability development to establish the relevance between the learning assigned to students and their future lives and work.